Surface-Displayed Amuc_1100 From Akkermansia muciniphila on Lactococcus lactis ZHY1 Improves Hepatic Steatosis and Intestinal Health in High-Fat-Fed Zebrafish - Zhang, Feng-Li; Yang, Ya-Lin; Zhang, Zhen; Yao, Yuan-Yuan; Xia, Rui; Gao, Chen-Chen; Du, Dong-Dong; Hu, Juan; Ran, Chao; Liu, Zhen; Zhou, Zhi-Gang (Frontiers in Nutrition, 2021)
Abstract Fatty liver and intestinal barrier damage were widespread in most farmed fish, which severely restricts the development of aquaculture. Therefore, there was an urgent need to develop green feed additives to maintain host liver and intestinal health. In this study, a probiotic pili-like protein Amuc_1100 was anchored to the surface of Lactococcus lactis ZHY1, and the effects of the recombinant bacteria AM-ZHY1 on liver fat accumulation and intestinal health were evaluated. Zebrafish were fed basal diet, high fat diet and high fat diet with AM-ZHY1 (108 cfu/g) or control bacteria ZHY1 for 4 weeks. Treatment with AM-ZHY1 significantly reduced hepatic steatosis in zebrafish. qPCR detection showed that the expression of lipogensis gene (PPARγ, SREBP-1c, FAS, ACC1) and lipid transport genes (CD36, FABP6) in the liver were significantly down-regulated (P < 0.05), indicating that AM-ZHY1 could reduce liver fat accumulation by inhibiting lipid synthesis and absorption. Moreover, supplementing AM-ZHY1 to high fat diet could significantly reduce serum AST and ALT levels, indicating that liver injury caused by high fat diet was improved. The expression of TNF-a, IL-6 in the liver decreased significantly (P < 0.05), while IL-1β and IL-10 did not change significantly in AM-ZHY1 group. Compared to the high fat diet-fed group, the AM-ZHY1 group but not the ZHY1 group significantly increased the expression of intestinal tight junction proteins (TJP1a, claudina, claudin7, claudin7b, claudin11a, claudin12, claudin15a; P < 0.05). Compared to high fat diet-group, the Proteobacteria and Fusobacteria were significantly reduced and increased in AM-ZHY1 group, respectively. In conclusion, recombinant bacteria AM-ZHY1 has the capacity to maintain intestinal health by protecting intestinal integrity and improving intestinal flora structure and improve fatty liver disease by inhibiting lipid synthesis and absorption. This study will lay a foundation for the application of AM protein in improving abnormal fat deposition and restoring intestinal barrier in fish.